BALANCING IDEALS AND ACTION: EXAMINING THE INFLUENCE OF POLITICAL IDEOLOGIES ON ENVIRONMENTAL POLICY FORMULATION IN INDIA - George Joseph (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper examines the complex relationship between political ideology and environmental policymaking in India. It analyses the impact of political actors’ ideas and values on legislative goals, governance structures, and policy results in tackling the nation’s intricate environmental issues. This study examines historical patterns, ideological dynamics, and significant case studies to underscore the substantial influence of ideology on policy formation and implementation. It examines the issues presented by ideological polarisation and institutional limitations while proposing methods to promote collaborative and inclusive environmental governance.